2017
DOI: 10.1021/acs.organomet.7b00368
|View full text |Cite
|
Sign up to set email alerts
|

Bis(boryl anion)-Substituted Pyrenes: Syntheses, Characterizations, and Crystal Structures

Abstract: The two new diboranes 1 and 2 connected by a pyrene moiety at the 1,6- and 1,3-positions, respectively, were synthesized, and their two-electron-reduction reactions were investigated. The doubly reduced species 1 ••2– is silent in electron paramagnetic resonance (EPR) and nuclear magnetic resonance (NMR) spectroscopic measurements, suggesting a quasi-quinoidal structure with a diradical character of 1 ••2–, which has a singlet–triplet gap of 6.6 kcal mol–1 as determined by theoretical calculations. In contrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…4a ). The 11 B hyperfine coupling constant is smaller than those of I (6.43 G) 4 and isolable boron radical anions, 2 but comparable to those of II (≤1.18 G) 5 and reported stable neutral boron radicals (0.96–8.5 G). 3 The moderate a ( 11 B) coupling constant together with relative small a ( 14 N) values suggests delocalization of the unpaired electron over the B 2 N 4 C 2 core.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…4a ). The 11 B hyperfine coupling constant is smaller than those of I (6.43 G) 4 and isolable boron radical anions, 2 but comparable to those of II (≤1.18 G) 5 and reported stable neutral boron radicals (0.96–8.5 G). 3 The moderate a ( 11 B) coupling constant together with relative small a ( 14 N) values suggests delocalization of the unpaired electron over the B 2 N 4 C 2 core.…”
Section: Resultsmentioning
confidence: 65%
“…Boron-containing radicals have been extensively studied due to their importance in fundamental chemistry and promising applications in various organic syntheses involving radical reactions. 1 Thus far, a number of stable anionic 2 and neutral 3 boron radicals have been reported. By stark contrast, isolable boron radical cations are extremely rare probably due to the intrinsic electron deficient nature of boron.…”
Section: Introductionmentioning
confidence: 99%
“…Related 2,7‐diborylated pyrenes with fused phenoxy bridges were recently reported by Müllen, X.‐Y. Wang et al . The π‐annulation to phenyl rings in the 1,3,6,8‐positions led to a narrower HOMO–LUMO gap and a strong green fluorescence with a maximum intensity at 525 nm.…”
Section: Introductionmentioning
confidence: 77%
“…Indeed, Tan, X. Wang et al. later showed that the doubly reduced species adopts a quasi‐quinoidal structure and is EPR silent because it adopts a singlet ground state . In contrast, the isomeric 1,3‐diborylated species ( B ) adopts an open‐shell singlet state in its doubly reduced form with a small singlet–triplet gap and is therefore EPR active .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation